The health benefits and risks of sports: an overview of current research and recommendations for high-performance and recreational athletes / Dr. Farah Adilla Ab Rahman - Ab Rahman, Farah Adilla (Universiti Teknologi MARA, Negeri Sembilan, 2024)
“In high-performance sports, balancing performance with health is essential.” Introduction: Sports enhance physical health and psychosocial well-being, offering benefits like improved mental health and personal development. However, they also present risks such as injuries and burnout. This review explores the advantages and risks of sports and provides recommendations for improving athlete’s health. Benefits of Sports: Research shows sports offer many benefits. Regular activity enhances physical and mental health, with sports promoting psychosocial development and reducing alcohol use and mental illness [1]. Cycling lowers heart disease risk, football supports weight and cardiovascular health and running and swimming are linked to lower mortality rates and improved health [2].